Strategi Kompetitif Petani Dan Inovasi UMKM Terhadap Peningkatan Kemajukan Bisnis Pangan Modern - Elisabet Jessika Manurung; Anaria Zendrato; Jesika Melina Simamora (Journal of Innovative and Creativity, 2026)
This research aims to analyze the influence of competitive farmer strategies and Micro, Small, and Medium Enterprise (MSME) innovation on the advancement of modern food businesses. The agricultural sector is currently undergoing a significant transformation toward modernization, necessitating continuous innovation to maintain competitiveness in an increasingly stringent market. Employing a quantitative research methodology, this study utilized 30 consumer respondents as the primary sample. Data were collected through questionnaires and interviews, subsequently analyzed using SPSS 25 software through multiple linear regression analysis, validity and reliability tests, and classical assumption tests. The research findings indicate that the farmer variable partially exerts a significant influence on modern food business progress, with a significance value of 0.001. Similarly, the MSME innovation variable proved to provide a significant partial contribution, also yielding a significance value of 0.001. Simultaneously, the F-test results produced a significance value of 0.001 and an F-statistic of 120.235, which exceeds the F-table value of 3.34. These findings confirm that combined farmer strategies and MSME innovations possess a positive and significant impact on driving modern food business growth. This study concludes that the synergy between appropriate farmer strategy implementation and unique MSME innovation development is the primary key to accelerating the advancement of the modern food sector.